Building the Human Economy Together - Hart, Keith; Laville, Jean-Louis; Cattani, Antonio (The Human Economy. A Citizen’s Guide, 2010)
KM: We want to bring to the attention of English readers some currents of economic theory and practice that have flourished in non-Anglophone countries over the last two decades, particularly in France, Brazil, Hispanic America and Scandinavia. To these we have added significant work by English-speaking authors that was sidelined during neoliberalism’s heyday and deserves to find a wider audience now. We have brought these strands of new thinking together under the umbrella concept of ‘the human economy’ which refers to an emphasis both on what people do for themselves and on the need to find ways forward that must involve all of humanity somehow.
Anthropology
Keywords: human economy; solidarity economy